Worse Health-Related Quality of Life at long-term follow-up in patients with Cushing's disease than patients with cortisol producing adenoma. Data from the ERCUSYN - Valassi, Elena; Feelders, Richard; Maiter, Dominique; Chanson, Philippe; Yaneva, Maria; Reincke, Martin; Krsek, Michal; Tóth, Miklós; Webb, Susan M; Santos, Alicia; Paiva, Isabel; Komerdus, Irina; et al. (Clinical endocrinology, 2018)
OBJECTIVE: Hypercortisolism in Cushing's syndrome (CS) is associated with impaired health-related quality of life (HRQoL), which may persist despite remission. We used the data entered into the European Registry on Cushing's syndrome (ERCUSYN) to evaluate if patients with CS of pituitary origin (PIT-CS) have worse HRQoL, both before and after treatment than patients with adrenal causes (ADR-CS). METHODS: Data from 595 patients (492 women; 83%) who completed the CushingQoL and/or EQ-5D questionnaires at baseline and/or following treatment were analysed. RESULTS: At baseline, HRQoL did not differ between PIT-CS (n = 293) and ADR-CS (n = 120) on both EuroQoL and CushingQoL. Total CushingQoL score in PIT-CS and ADR-CS was 41 ± 18 and 44 ± 20, respectively (P = .7). At long-time follow-up (>1 year after treatment) total CushingQoL score was however lower in PIT-CS than ADR-CS (56 ± 20 vs 62 ± 23; P = .045). In a regression analysis, after adjustment for baseline age, gender, remission status, duration of active CS, glucocorticoid dependency and follow-up time, no association was observed between aetiology and HRQoL. Remission was associated with better total CushingQoL score (P < .001), and older age at diagnosis with worse total score (P = .01). Depression at diagnosis was associated with worse total CushingQoL score at the last follow-up (P < .001). CONCLUSION: PIT-CS patients had poorer HRQoL than ADR-CS at long-term follow-up, despite similar baseline scoring. After adjusting for remission status, no interaetiology differences in HRQoL scoring were found. Age and presence of depression at diagnosis of CS may be potential predictors of worse HRQoL regardless of CS aetiology.
Keywords: dospělí; Adenoma; průzkumy a dotazníky; Female; hypersekrece ACTH v hypofýze; Quality of Life; Adult; ženské pohlaví; Surveys and Questionnaires; hydrokortison; adenom; kvalita života; lidé; Hydrocortisone; glukokortikoidy; Glucocorticoids; prospektivní studie; Male; Pituitary ACTH Hypersecretion; Prospective Studies; lidé středního věku; mužské pohlaví; Middle Aged; Humans